Efficacy of a Brief Gratitude Intervention on Psychological Well-being Among Male University Students in Sindh, Pakistan: https://doi.org/10.5281/zenodo.17435828 - Farhat Jokhio, PhD; Muhammad Rizwan*, PhD (Journal of Religion and Society, 2025)
This research aimed to determine whether the gratitude intervention may improve the level of psychological well-being (PWB) among male university students. A single-group, pretest-posttest quasi-experimental design was employed to test the hypothesis. The first phase involved screening of 80 participants (40 female, 40 male) aged 19 to 24 for gratitude and Psychological Well-being. Analysis of data revealed that male participants scored significantly lower on both gratitude and well-being as compared to their female counterparts. Afterward, twenty (20) male students were recruited for the gratitude intervention, which required them to write "three good things" every night for 10 days. Findings of the post-intervention confirmed a significant increase in both gratitude and psychological well-being scores within the cohort. This has specific implications in the collectivist-based culture of Sindh, Pakistan, and contributed to positive psychology in general. Keywords: Gratitude Intervention, Psychological Well-being, Male University Students, Sindh, Pakistan, Positive Psychology